2002
DOI: 10.1063/1.1506922
|View full text |Cite
|
Sign up to set email alerts
|

Vortex control of bifurcating jets: A numerical study

Abstract: Direct and large-eddy simulations (DNS/LES) are performed to analyze the vortex dynamics and the statistics of bifurcating jets. The Reynolds number ranges from ReD=1.5×103 to ReD=5.0×104. An active control of the inlet conditions of a spatially evolving round jet is performed with the aim of favoring the jet spreading in one particular spatial direction, thus creating a bifurcating jet. Three different types of forcing, based on the information provided by a LES of a natural (unforced) jet, are superimposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
74
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 28 publications
14
74
0
2
Order By: Relevance
“…Numerical simulations performed with Direct Numerical Simulation (DNS) [10][11][12][13] and Large Eddy Simulation (LES) [14][15][16] reproduced and confirmed these experimental results. Moreover, new findings were revealed, among others, for low Reynolds number jets (Re = 1500) the flapping excitation is sufficient to obtain jet bifurcation and there is no need to also include the axial excitation [12] as was later confirmed in [15]. Such behaviour was attributed to the existence of strong primary vortex rings which at low Reynolds number are not distorted by natural turbulence or flapping forcing.…”
supporting
confidence: 52%
See 3 more Smart Citations
“…Numerical simulations performed with Direct Numerical Simulation (DNS) [10][11][12][13] and Large Eddy Simulation (LES) [14][15][16] reproduced and confirmed these experimental results. Moreover, new findings were revealed, among others, for low Reynolds number jets (Re = 1500) the flapping excitation is sufficient to obtain jet bifurcation and there is no need to also include the axial excitation [12] as was later confirmed in [15]. Such behaviour was attributed to the existence of strong primary vortex rings which at low Reynolds number are not distorted by natural turbulence or flapping forcing.…”
supporting
confidence: 52%
“…In the present study we add the excitation as a component of the velocity prescribed at the inlet. Similarly as in [12,15,16] the inlet velocity profile used in the present work is defined as:…”
Section: Inlet Excitation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…process is also observed in the numerical study of a bifurcating jet [40]. In that study, it was reported that the jet splits into two separate jets.…”
Section: Flow Structure Developmentmentioning
confidence: 66%